APAKAH BIG DATA ANALYTICS CAPABILITY MENINGKATKAN NILAI BISNIS DAN KINERJA PERUSAHAAN: STUDI KASUS INDONESIA - Mochamad Chairul Ihsan (Gapenas Publisher, 2023)
In the era of data economy, the development of Big Data Analytics Capability (BDAC) has changed the face of competitiveness in many sectors. Organizations have intensively utilized BDAC as a competitive force to improve firm performance. Conveying from the resource-based view and sociomaterialism entanglement, BDAC has a huge potential to enhance business value and firm performance. This study extends the literature on BDAC impacts on organizations, especially in developing countries, by proposing a model and validating the direct effects of BDAC on firm performance and business value, along with the mediating effects of business value on the relationship between BDAC and firm performance. Toward this goal, an online survey was conducted and collected 86 data from IT managers, business analysts, and data analyst that are currently working in companies that have implemented Big Data Analytics (BDA) in Indonesia. The data was afterward analyzed using Partial Least Square Structural-Equation Model (PLS-SEM). The findings showed that BDAC has a positive impact on firm performance in terms of financial and market performance relative to competitors. The results also revealed that BDAC enhances business value. However, it was found that there is no significant mediating effects of business value on the relationship between BDAC and firm performance